Direction-specific postural instability in subjects with Parkinson's disease - Horak, Fay B.; Dimitrova, Diana; Nutt, John G. (Experimental neurology, 2005)
The purpose of this study was to determine whether and why subjects with Parkinson's disease (PD) have greater instability in response to specific directions of perturbations than do age-matched control subjects and how instability is affected by stance width. This study compared postural responses to 8 directions of surface translations in PD subjects and age-matched control subjects while standing in a narrow and wide stance. PD subjects were tested in their practical OFF state. A postural stability margin was quantified as the difference between peak center of pressure (CoP) and peak center of mass (CoM) displacement in response to surface translations. The control subjects maintained a consistent stability margin across directions of translations and for both narrow and wide stance by modifying rate of rise of CoP responses. PD subjects had smaller than normal postural stability margins in all directions, but, especially for backwards sway in both stance widths and for lateral sway in narrow stance width. The reduced stability margin in PD subjects was due to a slower rise and smaller peak of CoP in the PD subjects than in control subjects. Lateral postural stability was compromised in PD subjects by lack of trunk flexibility and backwards postural stability was compromised by lack of knee flexion, resulting in excessive displacements of the body CoM. Stability margins in PD subjects were related to their response on the pull test in the Unified Parkinson's Disease Rating Scale. Thus, PD patients have directionally specific postural instability due to an ineffective stiffening response and inability to modify their postural responses for changing postural demands related to direction of perturbation and initial stance posture. These results suggest that the basal ganglia, in addition to regulating muscle tone and energizing postural muscle activation, also are critical for adapting postural response patterns for specific biomechanical conditions.